Pengembangan Aplikasi My Edu-VegFruit Berbasis Android untuk Meningkatkan Konsumsi Sayur dan Buah pada Remaja: Development of the Android-Based My Edu-VegFruit Application to Increase Vegetable and Fruit Consumption in Teenagers - Emilia, Esi; Mokmin, Nur Azlina Mohamed; Hanifa, Zulfa Nur; Juliarti, Juliarti (Universitas Airlangga, 2024)
Background: Many adolescents are unaware of the importance of consuming sufficient vegetables and fruits for maintaining good health. One of the contributing factors is their lack of understanding about how to assess their daily vegetable and fruit intake to meet nutritional needs. Therefore, there is a need to develop an Android-based application to help increase vegetable and fruit consumption among adolescents. Objectives: To develop the android-based “My Edu-VegFruit” application as a guide to understand and increase vegetable and fruit consumption in adolescents. Methods: The study was conducted from March to November, 2024 at the Faculty of Engineering, State University of Medan. The research sample consisted of 120 students from the 2022 Nutrition Study Program cohort, selected through purposive sampling. This research employed a research and development (R&D) method using the Four-D model. Results: The define phase analysis revealed that only 20% of the sample understood their daily vegetable requirements, and 48.9% understood their fruit needs. A total of 87% of respondents expressed the need for the application. The identification phase determined the content to be included in the application. During the design phase, a complete storyboard for the application, including supporting features, was created according to the research objectives. The develop phase involved media and material validation by experts, yielding feasibility ratings of 92% from material experts and 91.67% from media experts, both categorized as highly feasible. In the disseminate phase, the application trial showed an increase in knowledge about vegetable and fruit requirements to 80%. Additionally, 90% of the sample reported satisfaction with the application. Conclusions: The “My Edu-VegFruit” application is considered highly feasible as a guide for calculating vegetable and fruit requirements among adolescents. It can also serve as an educational tool for nutrition education on vegetables and fruits.